Modelling the Determinants of Malaysian Household Debt - Khan, Hafizah Hammad Ahmad; Abdullah, Hussin; Samsudin, Shamzaeffa (International Journal of Economics and Financial Issues, 2016)
This paper explores the determinants of household debt composition in Malaysia. By utilizing the bound test and Autoregressive Distributed Lag (ARDL) modelling approach, findings of this study reveals that in the long run period, a change in income level, housing price and population would have a positive impact on mortgage debt while rise in interest rates and cost of living would exert a negative influence. In addition, findings of this study supported that the household uses the debt as a substitute for income to finance the rising consumption as a result of a higher living cost. Findings of this study could provide some guidance to policymakers in controlling the mounting debt level and help in realizing the nation economic goals. Keywords: Household debt, Mortgage debt, Consumer debt, Bound test, Auto-regressive distributed lag (ARDL) modelling JEL Classifications: E00, E21, E31, E43, E51, G00